PEMASARAN PRODUK MELALUI PROGRAM POJOK UMKM DI DESA KINDANG GUNA MENINGKATKAN EKSISTENSI PRODUK DAN MEMAJUKAN PEREKONOMIAN MASYARAKAT - Nurrahmah, Andi Tenrisau; Nuraeni, Siti; Jibriyanti, Jibriyanti; Yaqhsan, Muh (Transpublika Publisher, 2023)
Efforts in marketing products through the Micro, Small and Medium Enterprises or MSMEs Corner program play an important role in increasing the existence of products and the economic progress of the community in Kindang Village. This is based on the main problem of the decline in the community's economy as a result of the Covid-19 pandemic. For this reason, the MSME Corner program is present to facilitate business units in Kindang Village through marketing selected products to advance the economy of Kindang Village and expand the market or consumer reach of MSME players in Kindang Village. The implementers of this program are lecturers, students, along with mentors and village officials in Kindang Village. The visible achievement of this program is the availability of the UMKM Corner facility in Kindang Village. This facility not only functions as a marketing place, but also as an information and promotion center to expand market reach. Thus, this program not only provides direct economic benefits through increased product sales, but also indirectly increases public awareness and appreciation of local products. In addition, the program has a positive impact on increasing community involvement in local economic enterprises. With the MSME Corner, the community of Kindang Village can directly benefit from the development of micro, small and medium enterprises, thus increasing their sense of ownership and pride in their local products. This program can be used as an example for other villages as a model of effective collaboration in advancing the MSME sector at the local level.